EXPLORING PRACTICES OF SPEECH-LANGUAGE PATHOLOGISTS IN MANAGING LATE TALKER CASES - Nur Hanisah Tukiran; Mohamed Zain, Nor Azrita; Ahmad Basri, Nadzirah (International Journal of Allied Health Sciences, 2019)
Late talkers (LTs) are children aged 18-35 months old who are delayed in language development despite normal cognition, sensory and motor systems and absence of any structural and neurological problems. Intervention for LTs is usually given by speech-language pathologists (SLPs). Despite growing evidence regarding the importance of parental involvement in language intervention for LTs, it is unknown how much the involvement is considered by SLPs. Moreover, it is unclear what intervention practice includes. The aim of this study was to explore the practices of SLPs in managing LT cases. Twelve SLPs from different setting participated in individual, semi-structured phone interviews. They were asked about their clinical activities performed during language intervention for LTs. Recorded interviews were transcribed, and content analysis was performed. The resultsfound that the main clinical activities during managing LT cases include; assessing abilities, counselling, setting treatment goals andconducting therapy or training. Degree of parental involvement during the intervention is, however, varied. Results of this study offer some valuable insights into language intervention for LTs.